Bagha Jatin : life in Bengal and death in Orissa (1879-1915) - Mukherjee, Prithwindra (Manohar, 2016)
On the life and activities of Jyotindra Nath Mukherjee, 1880-1915, militant revolutionary in the Indian freedom movement